Are Lower Response Rates Hazardous to Your Health Survey? An Analysis of Three State Telephone Health Surveys - Davern, Michael; McAlpine, Donna; Beebe, Timothy J.; Ziegenfuss, Jeanette; Rockwood, Todd; Call, Kathleen Thiede (Health services research, 2010)
Objective. To examine the impact of response rate variation on survey estimates and costs in three health telephone surveys. Data Source. Three telephone surveys of noninstitutionalized adults in Minnesota and Oklahoma conducted from 2003 to 2005. Study Design. We examine differences in demographics and health measures by number of call attempts made before completion of the survey or whether the household initially refused to participate. We compare the point estimates we actually obtained with those we would have obtained with a less aggressive protocol and subsequent lower response rate. We also simulate what the effective sample sizes would have been if less aggressive protocols were followed. Principal Findings. Unweighted bivariate analyses reveal many differences between early completers and those requiring more contacts and between those who initially refused to participate and those who did not. However, after making standard poststratification adjustments, no statistically significant differences were observed in the key health variables we examined between the early responders and the estimates derived from the full reporting sample. Conclusions. Our findings demonstrate that for the surveys we examined, larger effective sample sizes (i.e., more statistical power) could have been achieved with the same amount of funding using less aggressive calling protocols. For some studies, money spent on aggressively pursuing high response rates could be better used to increase statistical power and/or to directly examine nonresponse bias.